2. 10°
36.00 / 75% = 0.48
0.48 x 100% =$48.00
B) SAS
D) ASA
E) AAS
F) HL
G)not congruent
Explanation:
AAS stands for Angle Angle Side. The order is important because the side is not between the angles.
The diagram shows that
Items 1 and 2 above correspond to the "A"s of "AAS", while item 3 refers to the "S".
Once again, the order of AAS is important. We don't go for ASA because side AB is not between angles A and C. Same for DE not between angles D and E.
Answer: -1/2x - 2.
Step-by-step explanation:
To find the quadratic function y = a(x-h) that passes through the points (6, -1) and (4, 0), we can substitute the given points into the equation and solve for a and h. Let's go through the steps:
1. Substitute the coordinates of the first point (6, -1) into the equation:
-1 = a(6 - h)
2. Substitute the coordinates of the second point (4, 0) into the equation:
0 = a(4 - h)
3. Now we have a system of two equations with two unknowns. We can solve this system to find the values of a and h.
From the equation -1 = a(6 - h), we can rewrite it as:
-a(6 - h) = 1
From the equation 0 = a(4 - h), we can rewrite it as:
-a(4 - h) = 0
4. Simplifying the equations, we get:
-6a + ah = 1 (equation 1)
-4a + ah = 0 (equation 2)
5. Subtracting equation 2 from equation 1 eliminates the ah term:
-6a + ah - (-4a + ah) = 1 - 0
-6a + ah + 4a - ah = 1
-2a = 1
6. Solving for a, we divide both sides by -2:
a = -1/2
7. Substitute the value of a back into either equation (let's use equation 2) to solve for h:
-4(-1/2) + h(-1/2) = 0
2 + h/2 = 0
h/2 = -2
h = -4
8. Now we have the values of a = -1/2 and h = -4. We can substitute these values back into the original equation y = a(x-h) to find the quadratic function:
y = -1/2(x - (-4))
y = -1/2(x + 4)
y = -1/2x - 2
Therefore, the quadratic function that passes through the points (6, -1) and (4, 0) is
AI-generated answer
To find the quadratic function y = a(x-h) that passes through the points (6, -1) and (4, 0), we can substitute the given points into the equation and solve for a and h. Let's go through the steps:
1. Substitute the coordinates of the first point (6, -1) into the equation:
-1 = a(6 - h)
2. Substitute the coordinates of the second point (4, 0) into the equation:
0 = a(4 - h)
3. Now we have a system of two equations with two unknowns. We can solve this system to find the values of a and h.
From the equation -1 = a(6 - h), we can rewrite it as:
-a(6 - h) = 1
From the equation 0 = a(4 - h), we can rewrite it as:
-a(4 - h) = 0
4. Simplifying the equations, we get:
-6a + ah = 1 (equation 1)
-4a + ah = 0 (equation 2)
5. Subtracting equation 2 from equation 1 eliminates the ah term:
-6a + ah - (-4a + ah) = 1 - 0
-6a + ah + 4a - ah = 1
-2a = 1
6. Solving for a, we divide both sides by -2:
a = -1/2
7. Substitute the value of a back into either equation (let's use equation 2) to solve for h:
-4(-1/2) + h(-1/2) = 0
2 + h/2 = 0
h/2 = -2
h = -4
8. Now we have the values of a = -1/2 and h = -4. We can substitute these values back into the original equation y = a(x-h) to find the quadratic function:
y = -1/2(x - (-4))
y = -1/2(x + 4)
y = -1/2x - 2
Therefore, the quadratic function that passes through the points (6, -1) and (4, 0) is y = -1/2x - 2.